Fading boundaries between the physical and the social world: Insights and novel techniques from the intersection of these two fields - Dapor, Cecilia; Sperandio, Irene; Meconi, Federica (Frontiers in Psychology, 2023)
This review focuses on the subtle interactions between sensory input and social cognition in visual perception. We suggest that body indices, such as gait and posture, can mediate such interactions. Recent trends in cognitive research are trying to overcome approaches that define perception as stimulus-centred and are pointing towards a more embodied agent-dependent perspective. According to this view, perception is a constructive process in which sensory inputs and motivational systems contribute to building an image of the external world. A key notion emerging from new theories on perception is that the body plays a critical role in shaping our perception. Depending on our arm’s length, height and capacity of movement, we create our own image of the world based on a continuous compromise between sensory inputs and expected behaviour. We use our bodies as natural “rulers'' to measure both the physical and the social world around us. We point out the necessity of an integrative approach in cognitive research that takes into account the interplay between social and perceptual dimensions. To this end, we review long-established and novel techniques aimed at measuring bodily states and movements, and their perception, with the assumption that only by combining the study of visual perception and social cognition can we deepen our understanding of both fields.